2014
DOI: 10.1007/s11274-014-1647-7
|View full text |Cite
|
Sign up to set email alerts
|

Biobleaching of Acacia kraft pulp with extracellular enzymes secreted by Irpex lacteus KB-1.1 and Lentinus tigrinus LP-7 using low-cost media

Abstract: The white-rot fungi Irpex lacteus KB-1.1 and Lentinus tigrinus LP-7 have been shown in previous studies to have high biobleaching activity in vivo. The aim of this study was to investigate the activities and stabilities of extracellular enzymes, prepared from I. lacteus and L. tigrinus culture grown in three types of economical media of agricultural and forestry wastes, for biobleaching of Acacia oxygen-delignified kraft pulp using kappa number reduction as an indicator of delignification. After 3 days of incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 43 publications
5
11
0
Order By: Relevance
“…From the three types of media, incubation with the WRBG culture supernatant resulted in a greater than expected Kappa number reduction, as compared with the WRB and WRBM culture media. The previous study has been shown that I. lacteus and T. tigrinus produces high organic acids (malonate and oxalate) in WBRG [16]. We suggest that the presence of organics acids in culture media containing glucose could be correlated with performance of lignolytic enzymes of white-rot fungi to degrade lignin residues in A-OKP.…”
Section: Fig 4 Xylanase Activity (A) and Cellulase Activity (B) In mentioning
confidence: 60%
See 4 more Smart Citations
“…From the three types of media, incubation with the WRBG culture supernatant resulted in a greater than expected Kappa number reduction, as compared with the WRB and WRBM culture media. The previous study has been shown that I. lacteus and T. tigrinus produces high organic acids (malonate and oxalate) in WBRG [16]. We suggest that the presence of organics acids in culture media containing glucose could be correlated with performance of lignolytic enzymes of white-rot fungi to degrade lignin residues in A-OKP.…”
Section: Fig 4 Xylanase Activity (A) and Cellulase Activity (B) In mentioning
confidence: 60%
“…1. Meanwhile, time-L. tigrinus refer to report previously [16]. We compared the production of lignolytic enzymes among the white-rot fungi, the results showed that versicolor, I. lacteus and L. tigrinus MnP, MIP, and Lac, but no LiP.…”
Section: Fig 4 Xylanase Activity (A) and Cellulase Activity (B) In mentioning
confidence: 69%
See 3 more Smart Citations